Labor und Household Mobility: Efficiency and Equilibrium - Wrede, Matthias (The annals of regional science, 2006)
This paper considers the allocation of resources when people choose separately their residence and the place of work. The purpose of the paper is threefold. First, it derives necessary conditions for an efficient distribution of workers and residents. Second, besides efficient allocations market equilibria are discussed. Third, the paper also develops a spatial model with local public goods and discusses within the framework the impact of local public goods on the distribution of people and vice versa.